Characterization and Antioxidant Activity of Banana Peels, Pineapple Peels, and Combination Extracts of both Peels as Raw Materials in the Development of Hard Candy - Pratiwi Apridamayanti; Hadi Kurniawan; Fajar Nugraha; Inarah - Fajriaty; Siti Nani Nurbaeti; Liza Pratiwi (Majalah Obat Tradisional, 2022)
Kepok banana and pineapple are horticultural commodities found in West Kalimantan. The two fruits are generally used as processed foods such as fried bananas and pineapple jam. The use of fruit as food often leaves the peel as a by-product, which can produce waste twice the weight of the food consumed. Meanwhile, waste utilization is an innovation in food processing into functional products which are developed into hard candy. Therefore, this research aims to the specific and non-specific characterization of raw materials for making candy, namely the combination of banana and pineapple peel extract (KP-KN). The characterization is organoleptic tests on the content of ethanol-soluble and water-soluble extracts. The Total phenolic content was determined by the Follin ciocalticeu method with UV/Vis spectrophotometry. Furthermore, antioxidant activity tests with DPPH and FRAP methods using UV/Vis spectrophotometry and ELISA to determine antioxidant activity. The mineral content was observed using the molybdate vandalate method with UV/vis spectrophotometry and ICP-MS, Heavy metal contamination using the ICP-MS tool, and microbial contamination using the plate method. Moreover, the infundation process was carried out on banana and pineapple peels, and the results were evaporated using a food dehydrator to obtain a combination extract. The results showed that the organoleptically KP-KN combination extract had a bitter taste, pineapple smells, 15.57% ash content, ethanol soluble extract content of 55.10%, and 47.99% water-soluble extract. Also, the total phenolic of 6.22 g/Kg, as well as the mineral content of Potassium (K), Calcium (Ca), Iron (Fe), Magnesium (Mg), Zinc (Zn), and Phosphorus (P), which were 47.23 g/Kg, 291.43 mg/Kg, <1x10-6 g/Kg, 2.59x10-3 g/Kg, and 2.38 g/Kg, respectively. Meanwhile, the heavy metal and bacterial contamination test showed that Arsenic (As), Sn, Mercury (Hg), and lead (Pb) were <1x10-6 g/Kg and Cadmium (Cd) was 0.0293. In the microbial contamination test with bacterial components including the ALT test, a value of 4.83 x 103 cfu/g was found, and there was no contamination from E.coli, mold, and yeast bacteria, DPPH and FRAP methods showed antioxidant activity combination extract banana peels and pineapple peels with values of 1390.96±2.83 mg/L and 4542.81±1.10 mg/L compare antioxidant activity of ascorbic acid as standard is 2.13 mg/L and 4.83 mg/L. The test with the KP-KN combined extract can be used as a raw material for making hard candy because it contains minerals needed by the body, meets the safety and quality requirements of traditional medicines, and has antioxidant activity in vitro.